Clay Minerals Change the Toxic Effect of Cadmium on the Activities of Leucine Aminopeptidase - Shunyu Huang; Jingji Li; Jipeng Wang (Adsorption Science & Technology)
Soil leucine aminopeptidase (LAP) is a hydrolytic enzyme involved in the acquisition of nitrogen by microorganisms. In contaminated soils, LAP activity is affected not only by the type and concentration of heavy metals but also by the form of enzyme. Here, we investigated the degree and mechanism of cadmium (Cd) inhibition of soil LAP and purified LAP. We also examined the effect of montmorillonite and kaolinite on LAP and LAP contaminated with Cd. The results showed that Cd inhibition of LAP activity increased with increasing Cd concentration and that Cd exerted noncompetitive inhibition of LAP. The addition of clay minerals decreases LAP activity and the maximum reaction rate (Vmax), regardless of the presence of Cd. Montmorillonite decreases the affinity of LAP to the substrate (Km), while kaolinite increases the affinity of LAP to the substrate. The clay mineral-immobilized LAP showed an increase in resistance to Cd contamination compared with the free LAP. The results obtained in this study may aid in understanding the toxic effects of heavy metals on soil enzymes.